Aktualisasi Konsep Tabayyun Dalam Al-Qur'an Dan Hadis Sebagai Kerangka Etika Menghadapi Deepfake Dan Hoaks Berbasis Artificial Intelligence Di Era Digital - Hasbi Maulana Effendi; Anisa Rahmadani; Alvino Dwi Putra; Arif Alhakim; Ridho Frengky Pardiansyah (Journal of Sustainable Education, 2026)
The development of Artificial Intelligence (AI) has given rise to the phenomenon of deepfakes, the manipulation of audio, images, and videos capable of displaying false information with a high degree of similarity to reality. This phenomenon amplifies the spread of hoaxes and disinformation, potentially threatening information integrity, social stability, and public trust. This study aims to analyze the concept of tabayyun in the Qur'an and hadith and reconstruct it as an Islamic ethical framework for dealing with AI-based hoaxes and deepfakes. The method used is qualitative research with a library research approach through thematic analysis of Qur'anic verses, hadith, classical and contemporary commentaries, and literature related to digital literacy and deepfakes. The results show that tabayyun functions not only as an information verification mechanism but also as an Islamic epistemological paradigm that includes source validation, content verification, consideration of social impacts, and moral responsibility in disseminating information. In the context of deepfakes, tabayyun is relevantly developed as an Islamic digital literacy model that integrates critical thinking, technological verification, and ethical awareness to prevent the spread of false information in the era of artificial intelligence.